2020
DOI: 10.1155/2020/7413689
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Microbial, and Chemical Quality of Hot-Air-Dried Persimmon (Diospyros kaki) Chips during Storage

Abstract: Recent efforts have been made to develop hot-air-dried chips as a value-added product for persimmon fruit (Diospyros kaki). However, the long-term quality of this product and its dependence on processing conditions and packaging type have not yet been explored. Hence, in this work, chips were prepared from “Hachiya” persimmon fruit in 2 ways: 2 mm thickness fruit slices, hot-air-dried for 5 hours (Preparation 2–5), and 6 mm slices, dried for 10 hours (Preparation 6–10). The dried chips were then packaged into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Thus, the final goal of this work was to address this knowledge gap and give growers/processors some guidance for cultivar selection for hot-air drying. This goal is in support of a larger project on enhancing the marketability of persimmons grown in the U.S. State of California; other aspects of the larger project have been reported in our previous works [ 1 , 2 , 30 ].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, the final goal of this work was to address this knowledge gap and give growers/processors some guidance for cultivar selection for hot-air drying. This goal is in support of a larger project on enhancing the marketability of persimmons grown in the U.S. State of California; other aspects of the larger project have been reported in our previous works [ 1 , 2 , 30 ].…”
Section: Introductionmentioning
confidence: 82%
“…To encourage more widespread consumption of persimmons, researchers have endeavored to develop a value-added product (a hot-air-dried persimmon “chip”) that is shelf-stable and easily produced. Several groups [ 1 , 2 , 3 , 4 , 5 , 6 ] have previously conducted exploratory studies of sliced, hot-air-dried persimmon chips. However, in-depth information on the texture of these products is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Persimmon fruit is one such fruit that has gained considerable attention as a potentially beneficial functional ingredient (Vinha et al , 2021). Owing to its sensory properties, rich nutrient content and potential industrial applications, Persimmon is a treasured in many countries (Milczarek et al , 2020; Santos et al , 2018; Kluge and Tessmar, 2018). It is an excellent source of various macro- and micro-nutrients and possesses lower fat content (Barea-Álvarez et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that apart from a clear decline in ascorbic acid, all four preparation and packaging combinations generated products that retained adequate nutritional, microbial, color, and texture quality all the way through the whole study. It is suggested that hot-air-drying persimmon slices is an encouraging method to create a product with added-value that has a minimum of a one-year shelf-life [ 177 ]. Partial least-squares regression (PLS) was employed to create models that predicted the sensory characteristics from instrumental measurements, and models that predicted the consumer liking score from both instrumental measurements and sensory attributes.…”
Section: Introductionmentioning
confidence: 99%